Implementasi artificial neural network dalam mendeteksi penyakit hati (liver) - Irmawati Irmawati; Kudiantoro Widianto; Faruq Aziz; Achmad Rifai; Ami Rahmawati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Acute liver disease can affect liver function, but can identify the patient's clinical and physical symptoms. One of the problems faced by society today is the delay in treatment of liver disease patients, most patients do not carry out self-examination until an advanced stage is found. To overcome this problem, we need a system that can determine whether a person is a patient with liver disease, so that they can carry out routine checks as soon as possible and allow liver disease patients to get timely treatment. The system can generate classification with the help of data mining algorithms. In this paper, Liver Patients have been investigated using an Artificial Neural Network model to predict a Liver Patient or not and analysis using ANN with Python was used to determine the effect of input variables based on data in the literature and obtained an accuracy of 74%.